The relationship between emotional intelligence, anxiety, and performance in physical education and sport students - Zoghlami, Wael; Hawani, Aymen; Khiari, Hyem; Mnedla, Sofiene; Marsigliante, Santo; Elloumi, Ali; Muscella, Antonella (Frontiers in Psychology, 2023)
Emotional intelligence (EI) has been recently the main target in research on sports psychology. The objectives of this study were to investigate the relation between self-report measures of emotional intelligence, pre-competitive anxiety, and performance among students during the physical education exam of the high school final year. This cross-sectional study was conducted on a sample of 350 students attending the physical education exam in the year 2021–2022. Analysis of the correlations between the scores of Emotional intelligence and anxiety showed that self-confidence was positively correlated with all dimensions of Emotional intelligence (Beta = 0.524; p = 0.000). Multivariate linear regression analysis showed that the most related items to performance were self-confidence in a positive direction (r = 0.56; p = 0.000) and negatively with somatic anxiety (r = −0, 39; p = 0.000). Considering the Emotional intelligence subscales, hetero-emotional management was significantly positively associated with performance (p = 0.000) however emotional perception was negatively correlated with performance (p = 0.003). These results demonstrate the importance of social and emotional learning programs for improving self-confidence and better management of emotions during physical education and sports.